Listening to patients, for the patients: The COVAD Study—Vision, organizational structure, and challenges - Joshi, Mrudula; Darooka, Naitica; Saha, Sreoshy; Dyball, Sarah; Sen, Parikshit; Yaadav, Praggya; Javaid, Mahnoor; Kadam, Esha; Shinjo, Samuel Katsuyuki; Dey, Dzifa; Cavagna, Lorenzo; Makol, Ashima; et al. (International Journal of Rheumatic Diseases, 2024)
Background: The pandemic presented unique challenges for individuals with autoimmune and rheumatic diseases (AIRDs) due to their underlying condition, the effects of immunosuppressive treatments, and increased vaccine hesitancy. Objectives: The COVID-19 vaccination in autoimmune diseases (COVAD) study, a series of ongoing, patient self-reported surveys were conceived with the vision of being a unique tool to gather patient perspectives on AIRDs. It involved a multinational, multicenter collaborative effort amidst a global lockdown. Methods: Leveraging social media as a research tool, COVAD collected data using validated patient-reported outcomes (PROs). The study, comprising a core team, steering committee, and global collaborators, facilitated data collection and analysis. A pilot-tested, validated survey, featuring questions regarding COVID-19 infection, vaccination and outcomes, patient demographics, and PROs was circulated to patients with AIRDs and healthy controls (HCs). Discussion: We present the challenges encountered during this international collaborative project, including coordination, data management, funding constraints, language barriers, and authorship concerns, while highlighting the measures taken to address them. Conclusion: Collaborative virtual models offer a dynamic new frontier in medical research and are vital to studying rare diseases. The COVAD study demonstrates the potential of online platforms for conducting large-scale, patient-focused research and underscores the importance of integrating patient perspective into clinical care. Care of patients is our central motivation, and it is essential to recognize their voices as equal stakeholders and valued partners in the study of the conditions that affect them.
CRIS-Team Scopus Importer:2024-05-17
Keywords: autoimmune; collaboration; digital; PROMs; research; rheumatology; survey